Tradition of the Lvov-Warsaw school : ideas and continuations - Brożek, Anna. (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2016)
The volume aims to show the variety of research currents of the Lvov-Warsaw School and the ways in which these currents are developed today. The content of the book is divided into three parts. The first part provides an overview of the logico-semiotical achievements of the Lvov-Warsaw School. It also includes analyses of specific problems: categorial grammar, theory of truth, theory of reasoning and semiotic defects. The second part presents some metaphysical and ontological views of Twardowski, Kotarbiński, Ajdukiewicz, Bocheński and Lejewski. In the third part, specific features of psychological and sociological branches of the Lvov-Warsaw School are discussed. Contributors include: Anna Brożek, Wojciech Buszkowski, Alicja Chybińska, Mariusz Grygianiec, Aleksandra Horecka, Stepan Ivanyk, Jacek Jadacki, Ryszard Kleszcz, Natalia Miklaszewska, Wioletta Miśkiewicz, Teresa Rzepa, Piotr Surma, Jan Woleński, and Marta Zaręba.